Dead man walking : the eyewitness account of the death penalty that sparked a national debate - Prejean, Helen (Vintage Books, a division of Random House, Inc., 2013)
In 1982, Sister Helen Prejean became the spiritual advisor to Patrick Sonnier, a convicted killer sentenced to die in Louisiana's electric chair.